Postpartum women's views on human milk banking in a city in Southeast China: a cross-sectional survey - Haixia Tu; Ping Li; Lianlian Zhu; Xiaozhen Quan; Shuli Fan; Ziyue Wang (BMC, 2022)
Abstract Background Donor human milk is the best alternative for preterm infants when their mother's own milk is insufficient or unavailable. The development of human milk banks in China started late, and in most of these banks, the amount of donor human milk is insufficient for clinical demand. Moreover, many mothers are reluctant to use donor human milk due to safety concerns. It is important to understand the potential supply and demand of donor human milk before establishing a new human milk bank. This study aimed to understand women's acceptance of human milk banking in Wenzhou, southeastern China. Methods A cross-sectional study was conducted in three community health centers in Wenzhou, southeast China, in December 2020. Data were collected from 305 postpartum women selected through convenience sampling. Sociodemographic, perinatal and breastfeeding characteristics, awareness and knowledge of human milk banking and willingness to donate human milk, and to accept donor human milk were assessed. Multivariable logistic regression analysis was used to explore independent predictors of willingness to donate human milk and to accept donor human milk. Results Only 17% (52/305) of our participants had heard of human milk banking prior to this survey. The prevalence of willingness to donate human milk and use donor human milk in our study was 73.4% (224/305) and 44.6% (136/305), respectively. Employment (adjusted odds ratio [AOR] 2.30; 95% confidence interval [CI] 1.17, 4.50) and human milk banking knowledge (AOR 1.23; 95% CI 1.12, 1.35) were independent predictors of willingness to donate human milk. Monthly household income in the previous year (AOR 2.18; 95% CI 1.17, 4.06), awareness of human milk banking (AOR 2.41; 95% CI 1.24, 4.67) and knowledge of human milk banking (AOR 1.22; 95% CI 1.11, 1.35) were significantly associated with willingness to accept donor human milk. Conclusions In our study, awareness of human milk banks among women in the first year postpartum was low. More mothers were willing to donate human milk than to use donor human milk to feed their children. In our study, knowledge of human milk banking was a predictor of both willingness to donate human milk and willingness to use donor human milk. Programs with detailed information on human milk banking are needed to help mothers improve their knowledge and increase acceptance of human milk banking.